Embodiment, Semantics and Social Action: The Case of Object-Transfer in L2 Classroom Interaction - Eskildsen, S. W. (Frontiers in Communication, 2021)
Using conversation analysis and usage-based linguistics, I focus on a beginning L2 user in an ESL classroom and trace the emergence of a "family of expressions" which, from the perspective of linguistic theory, are instantiations of either the generalized ditransitive construction or a prepositional paraphrase ("he told the story to me") (Goldberg, 1995). The semantics of both constructions denotes transfer of an object, physically or metaphorically, from one agent to another. Therefore, I investigate them as one type of object-transfer construction. I show how the L2 user builds this construction on the basis of recurring exemplars in a locally contextualized, fundamentally embodied manner that is concretely rooted in social experience. The data show that the L2 user co-employs talk and recycled embodied work that elaborates the deictic references of the talk and the relation of agent-object-recipient roles among them. Through my analyses, I will showcase the embodied nature of linguistic categorization (Langacker, 1987) but take the argument further and suggest that the semiotic resource known as “language” is a residual of embodied social sense-making practices (aus der Wieschen & Eskildsen, 2019), as the L2 user appropriates the object-transfer construction predominantly in and through instruction sequences. The study draws on the MAELC database at Portland State University, a longitudinal audio-visual corpus of American English L2 classroom interaction.